Iowa Birdline update, January 13, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for January 13, 1992. The highlights for the update include sightings of an adult Great Black-backed Gull, Lesser Black-backed Gull, Glaucous Gull and other gull species. In addition to the gulls there were Common Redpolls and two adult Tundra Swans. Also included are handwritten notes with sightings of a Red-shouldered Hawk and a Yellow-bellied Sapsucker. Epson - sheet feed/flatbed